Phosphoglycerate Dehydrogenase: Potential Therapeutic Target and Putative Metabolic Oncogene - Zogg, Cheryl K. (J Oncol, 2014)
Exemplified by cancer cells' preference for glycolysis, for example, the Warburg effect, altered metabolism in tumorigenesis has emerged as an important aspect of cancer in the past 10–20 years. Whether due to changes in regulatory tumor suppressors/oncogenes or by acting as metabolic oncogenes themselves, enzymes involved in the complex network of metabolic pathways are being studied to understand their role and assess their utility as therapeutic targets. Conversion of glycolytic intermediate 3-phosphoglycerate into phosphohydroxypyruvate by the enzyme phosphoglycerate dehydrogenase (PHGDH)—a rate-limiting step in the conversion of 3-phosphoglycerate to serine—represents one such mechanism. Forgotten since classic animal studies in the 1980s, the role of PHGDH as a potential therapeutic target and putative metabolic oncogene has recently reemerged following publication of two prominent papers near-simultaneously in 2011. Since that time, numerous studies and a host of metabolic explanations have been put forward in an attempt to understand the results observed. In this paper, I review the historic progression of our understanding of the role of PHGDH in cancer from the early work by Snell through its reemergence and rise to prominence, culminating in an assessment of subsequent work and what it means for the future of PHGDH.